2013
DOI: 10.5732/cjc.011.10258
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alpha-308G/A polymorphism and risk of hepatocellular carcinoma in hepatitis C virus-infected patients

Abstract: Tumor necrosis factor-alpha (TNF-α) is an important cytokine in generating an immune response against infection with hepatitis C virus (HCV). The functions of TNF-α may be altered by single-nucleotide polymorphisms (SNPs) in its gene structure. We hypothesized that SNPs in TNF-α may be important in determining the outcome of an HCV infection. To test this hypothesis, we investigated the role of the polymorphism -308G/A, which is located in the promoter region of the TNF-α gene, in the progression of HCV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Of note, TNF- α is also induced by NF- κ B in a positive feedback loop. TNF- α levels in HCC patients have also been investigated, but controversial data have been reported, whereas TNF- α (308) single nucleotide polymorphism was associated with cancer susceptibility [70]. …”
Section: Tam-derived Factors In Hccmentioning
confidence: 99%
“…Of note, TNF- α is also induced by NF- κ B in a positive feedback loop. TNF- α levels in HCC patients have also been investigated, but controversial data have been reported, whereas TNF- α (308) single nucleotide polymorphism was associated with cancer susceptibility [70]. …”
Section: Tam-derived Factors In Hccmentioning
confidence: 99%
“…In a study by Kakumu et al TNF-αRs correlated with disease progression and IFN-α treatment did not affect their level (162). Regardin TNF-α polymorphism, the TNF-α (-308) SNP (single nucleotide polymorphisms) in the promoter region of the gene, which includes TNF-α1 (-308G) and TNF-α2 (-308A) alleles, is associated with cancer susceptibility and induced expression of TNF-α (153,(165)(166)(167).…”
Section: Hepatic Stellate Cells (Hscs)mentioning
confidence: 99%
“…Several reports have addressed possible implications of TNF‐α and IL‐10 promoter polymorphisms in HCV outcome; however, results have been inconsistent. Some studies have found significant correlation between the AA genotype of TNF‐α ‐308 and increased risk to cirrhosis or HCC [Yee et al, ; Dai et al, ; Jeng et al, , ; Feng et al, ; Radwan et al, ], on the other hand other studies failed to demonstrate significant association [Yu et al, ; Kusumoto et al, ; Dogra et al, ; Talaat et al, ; Corchado et al, ]. Regarding IL‐10, some studies indicated that patients with low IL‐10 production genotypes had a higher risk of liver cirrhosis and HCC [Bouzgarrou et al, , ], whereas other studies failed to confirm this association [Knapp et al, ; Abbott et al, ; Kusumoto et al, ; Paladino et al, ; Dogra et al, ; Ishida et al, ].…”
Section: Introductionmentioning
confidence: 99%